2016
DOI: 10.1007/s00432-015-2103-2
|View full text |Cite
|
Sign up to set email alerts
|

Primary gastric tumors in infants and children: 15 cases of 20-year report

Abstract: Owing to the atypical and often asymptomatic presentation of primary gastric tumors, careful evaluation using imaging modalities is critical in suspicious cases. Most primary gastric tumors in infants and children are benign or borderline. The prognosis, except in gastric carcinoma, is excellent with close follow-up when complete resection is achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…As shown in Supplementary Tables S1 and S2, this is the first prospective Italian cooperative study on GI carcinomas. All the previous studies on GI tract carcinomas in young people in the last 30 years were retrospective single‐institution series concerning only a handful of cases seen over broad periods of time, and most of them concerned patients ≤30 years of age. The only reports with a more substantial body of data are those published by tumor registries (e.g., Surveillance, Epidemiology and End Results).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Supplementary Tables S1 and S2, this is the first prospective Italian cooperative study on GI carcinomas. All the previous studies on GI tract carcinomas in young people in the last 30 years were retrospective single‐institution series concerning only a handful of cases seen over broad periods of time, and most of them concerned patients ≤30 years of age. The only reports with a more substantial body of data are those published by tumor registries (e.g., Surveillance, Epidemiology and End Results).…”
Section: Discussionmentioning
confidence: 99%
“…Wen et al (13) reported that 11.3% of patients with gastric cancer had bone metastasis, and median overall survival time was 6.5 months. Zheng et al (14) reported that a patient with gastric adenocarcinoma with liver and left supraclavicular lymph node metastasis underwent palliative tumor resection, but the patient died three months after diagnosis. The second case of our report was admitted to the hospital with leg pain due to bone metastasis and she died in a short time due to diffused metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, GB tumors are characterized by two components, the epithelial and the mesenchymal one, represented in variable portion, both with low-grade features, large tumor size, relatively low-mitotic activity, low overall atypia, absence of conspicuous nuclear pleomorphism and low malignant potential. Normally, the disease is delimited to the stomach, without metastatic potential or disease recurrence after curative resection [1, 2, 4–6, 8]. Nonetheless, two young adult patients, respectively 28 and 29 years, reported lymph node involvement and distant metastases [3, 7].…”
Section: Discussionmentioning
confidence: 99%